Good Corporate Governance in the Public Service Agency (Case Study at University of Brawijaya Malang) - Anggriawan, Ferry Fambia; kholis, Nur (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2014)
This study was encouraged by one of the country's financial reform agenda, i.e. a shift from the traditional budgeting into a performance-based budgeting. By using the performance-based budgeting system, the use of government funds are no longer only the input-oriented, but rather the performance. The reform includes the implementation of good governance in every aspect of Government in Indonesia. In order to implement Good Governance at State Universities, the government established the Public Service Agency with the aim of improving the quality of higher education services to the public. The purpose of this study was to determine the application of the principles of Good Governance at the University of Brawijaya Malang. This research is a qualitative case study. The Method that used to collect data was the documentation or archival, interviews, and observations. The results revealed that the principles of Good Governance at the University of Brawijaya Malang has been well implementation. However, there are several obstacles in its the implementation, i.e. the management of Universitas Brawijaya less well, a lack of understanding about characteristic GCG itself, and some people still think that application of GCG it is less important. Keywords: Good Corporate Governance, Country's Financial Reform, Public Service Agency, State Universities